Gender differences in child investment behaviour among agricultural households: Evidence from the Lesotho Child Grants Programme - Ashwini Sebastian; Ana Paula de la O Campos; Silvio Daidone; Benjamin Davis; Ousmane Niang; Luca Pellerano (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
We examine the impacts of an unconditional cash transfer in Lesotho using an experimental impact evaluation design. We find that the cash transfer led to different outcomes for girls and boys, overall favouring secondary school-aged girls. Girls in this age group were less likely to miss school, spent more time at school, and faced a reduced time burden in household chores. While the general results are maintained in households with a married couple present, in de jure female-headed households, outcomes improved among secondary school-aged boys relative to secondary school-aged girls. By contrast, having the father as recipient was more likely to have positive impacts on girls' schooling, decrease boys' labour in farming while simultaneously increasing boys' labour input in household chores. This puts into question the existence of gender preferences in schooling in Lesotho and suggests that impacts on child welfare are influenced by time and labour constraints and by gender-based differences in opportunity costs of a child's time.
Keywords: D13; I38; I25; 330; cash transfers; gender; child schooling; child time use; child farm labour; female-headed households